L'anàlisi del discurs, entre l'oralitat i l'escriptura - Vicent Salvador (Caplletra: Revista Internacional de Filologia, 2015)
This paper is about the most general methodological problems of Discourse Analysis: The meaning and use of metalinguistic terms as "discourse" and "text", the scope of different schools and the incidence of orality/literacy distinction. the author suggests a global outlook of D. A. accounting for both oral and weitten discourse (conversation, letters, mass media discourse, literature, among other genres) by means og an integrative theory. Contributions from various schools must be integrated to account for this important dimension of linguistic variation, frequently diregarded or misleading in practice by linguistic therorists.